1980
DOI: 10.1128/aem.39.6.1191-1197.1980
|View full text |Cite
|
Sign up to set email alerts
|

Die-away kinetics of aerosolized bacteria from sprinkler application of wastewater

Abstract: A methodology for estimating, under field conditions, the microbial die-away constant (lambda) is presented. This constant may be used in predicting the aerosolized pathogenic microorganism concentrations downwind from a wastewater spray or aeration site by means of modified atmospheric diffusion equations. The mean lambda of Escherichia coli for very early morning runs was 8.8 X 10(-3)s-1, and that for afternoon runs was 6.6 X 10(-2)s-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…Although it used a thick sludge, a later study by Pillai et al (1996) reported a low risk associated with its disposal and only sporadic detection of aerosolized bacterial and viral faecal indicators. A likely explanation for the finding was reported previously by Teltsch et al (1980), who found that the numbers of aerosolized Escherichia coli were lowered by 1 log after between 10 s and 2 min depending on environmental conditions.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Although it used a thick sludge, a later study by Pillai et al (1996) reported a low risk associated with its disposal and only sporadic detection of aerosolized bacterial and viral faecal indicators. A likely explanation for the finding was reported previously by Teltsch et al (1980), who found that the numbers of aerosolized Escherichia coli were lowered by 1 log after between 10 s and 2 min depending on environmental conditions.…”
Section: Introductionsupporting
confidence: 57%
“…However, an early report of long-distance travel of bacteria was made by Sorber et al (1976) who reported that the recovery of coliforms as far as 200 m downwind from a sprinkler land-spreading wastewater. Although some authors have voiced concerns regarding the recovery efficiencies of aerosolized bacteria (Teltsch et al 1980;Brooks et al 2005), Chinivasagam and Blackall (2005) report that E. coli is present inside pig housing at up to 59 CFU m )3 of air and that there was no discernible influence between impaction and impingement-based sampling in the pig housing environment.…”
Section: Discussionmentioning
confidence: 99%
“…By means of a linear regression model (R) we reanalysed their data showing that a high correlation (r = 0.72) existed between the measured and modelled data, although borderline statistically significant (p = 0.07). Teltsch et al (1980) detected E. coli in air samples near an Israelian WWTP and used the Gaussian dispersion equation for prediction modelling. A highly significant correlation was found (r = 0.93, p ≈ 0.00).…”
Section: Wastewatermentioning
confidence: 99%
“…The fate of bioaerosols and extent of bioaerosol dissemination are dictated by biotic factors that control the viability of the aerosolized organisms and abiotic factors that control the release, transport, and dispersion of the organisms ( Lighthart and Mohr, 1987 ; Pedgley, 1991 ). Mathematical models describing the release of microorganisms from surfaces, adsorption of aerosolized organisms to surfaces, deposition of bioaerosols, and potential health effects have been reported in the literature ( Brooks, Tanner, Gerba, Haas, and Pepper, 2005 ; Dowd et al, 2000 ; Pasquill, 1961 ; Prier et al, 2001 ; Tanner et al, 2005 ; Teltsch et al, 1980 ). To estimate bioaerosol transport, it is essential to understand the release rates of the different organisms, the dispersion of the bioaerosols, and the deposition of the organisms.…”
Section: Bioaerosol Transport Modelsmentioning
confidence: 99%
“…Moreover, biosolid handling practices are quite different from location to location, because of the type of mechanical equipment used, application methods, and solids content of the biosolids. Nevertheless, mathematical transport models have been developed and used to predict the dispersion and deposition of bioaerosols from a variety of sources, such as wastewater treatment plants, solid waste facilities, agricultural operations, and effluent irrigation ( Adams and Spendlove, 1970 ; Lembke and Kniseley, 1980 ; Lighthart, 1984 ; Sorber et al, 1984 ; Teltsch et al, 1980 ). These models have been subsequently used to determine the potential health risks associated with land‐applied biosolids ( Brooks, Tanner, Gerba, Haas, and Pepper, 2005 ; Brooks, Tanner, Josephson, Gerba, Haas, and Pepper, 2005 ; Dowd et al, 2000 ; Tanner et al, 2005 ).…”
Section: Bioaerosol Transport Modelsmentioning
confidence: 99%